2016
DOI: 10.18632/oncotarget.13931
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects against arsenic trioxide-induced liver injury by the upregulation of Nrf2 expression through the activation of PI3K/AKT pathway

Abstract: Melatonin has been demonstrated to have anti-inflammatory and antioxidant effects. The aim of this study was to investigate the protective effects of melatonin on arsenic trioxide (As2O3)-induced toxicity in liver and oxidative stress in rats. The rats were injected with 3mg/kg As2O3 on alternate days and melatonin was given with an intraperitoneal injection (i.p.) 1 h before As2O3 treatment. On the 8th days, the rats were killed to determine liver histological injury, antioxidant activities and accumulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 20 publications
5
26
0
Order By: Relevance
“…The Akt pathway was affected quite differently in the diverse cell lines: p-Akt increased in DX3 cells, remained unaffected in WM-115 cells, while it dramatically decreased in breast cancer cell lines. Actually, melatonin was previously shown to inhibit Akt phosphorylation in MCF-7 [ 29 ] and MDA-MB231 cells [ 28 ]; though it was recently observed that melatonin could upregulate the PI3K/Akt pathway in other model systems [ 40 , 41 ], including a melanoma cell line [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Akt pathway was affected quite differently in the diverse cell lines: p-Akt increased in DX3 cells, remained unaffected in WM-115 cells, while it dramatically decreased in breast cancer cell lines. Actually, melatonin was previously shown to inhibit Akt phosphorylation in MCF-7 [ 29 ] and MDA-MB231 cells [ 28 ]; though it was recently observed that melatonin could upregulate the PI3K/Akt pathway in other model systems [ 40 , 41 ], including a melanoma cell line [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The consequence of Akt activation is the upregulation of peroxisome proliferator‐activated receptor gamma coactivator 1α (PGC‐1α) followed by upregulated Sirt3 expression and activity . Akt activation is then followed by the improvement of Nrf2 and HO‐1, which is associated with the elevated antioxidant enzymes SOD and GPX . Moreover, Akt activation by melatonin also retards ER stress via targeting GSK‐3β and VDAC .…”
Section: Target Of Melatonin In Cardioprotection Under Ir Injurymentioning
confidence: 99%
“…According to Wu Set al, HBSP inhibits hepatocyte apoptosis through PI3K/Akt pathway, suggesting that the intervention of inhibiting Akt activation or functional activity may have therapeutic value during the process. PI3K/Akt pathway was reported to be involved in tissue injuries, such as I/R‐induced renal injury, streptozotocin‐induced testicular injury and trioxide‐induced liver injury . Therefore, it is of great significance to take effective measures to regulate PI3K/Akt pathway at the molecular level in the treatment of these diseases.…”
Section: Discussionmentioning
confidence: 99%